2012
DOI: 10.1021/jp2063996
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study on the Role of Ceria Addition in TixCe1–xO2 Adsorbents for Thiophene Adsorption

Abstract: A Ti x Ce 1−x O 2 -based material has been reported as a potential adsorbent for ultradeep adsorptive desulfurization of liquid hydrocarbon fuels. To understand the roles of TiO 2 and CeO 2 in the adsorbent, density functional theory (DFT) calculations examined the energetics of adsorption site formation and corresponding thiophene adsorption energies on surfaces of TiO 2 anatase, CeO 2 , and Ce-doped anatase. Compared with pure anatase surfaces, thiophene binds more strongly to Ce-doped anatase surfaces. O-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
29
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 61 publications
5
29
3
Order By: Relevance
“…However, the free energy of adsorption of an O 2 molecule on stoichiometric Ce-TiO 2 surfaces with water dissociatively Table 2. Energetics of the Adsorption Cycle on the Pure and Doped (001) Surface in eV a sulfoxide reaction energy [3] sulfoxide activation barrier [3] sulfone reaction energy [4] (0,0,1) migration energy [5] (1,0,1) migration energy [5] (1,0,0) migration energy [ a Reaction step labels refer to Figure 1. The final migration step reaction energy is given with the sulfone migrating to any of the three surfaces considered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the free energy of adsorption of an O 2 molecule on stoichiometric Ce-TiO 2 surfaces with water dissociatively Table 2. Energetics of the Adsorption Cycle on the Pure and Doped (001) Surface in eV a sulfoxide reaction energy [3] sulfoxide activation barrier [3] sulfone reaction energy [4] (0,0,1) migration energy [5] (1,0,1) migration energy [5] (1,0,0) migration energy [ a Reaction step labels refer to Figure 1. The final migration step reaction energy is given with the sulfone migrating to any of the three surfaces considered.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption energy of molecular oxygen on stoichiometric TiO 2 and Ti-CeO 2 surfaces is close to 0 eV, 5,9 and the free energy of adsorption is significantly positive. Surface O vacancies, however, serve as active sites to trap O 2 and allow for subsequent adsorption for thiophene.…”
Section: Introductionmentioning
confidence: 86%
“…Computational studies suggested that chemisorbed oxygen species on the TiO 2 surface played an important role in promoting ADS, [14] thus suggesting highly selective adsorption through the formation of sulfoxide/sulfone species. [15] Our previous computational work [16] also suggested a number of possible effects of Ce addition to TiO 2 , although it only examined the adsorption thermodynamics and was inconclusive regarding the key impact of Ce addition. We hypothesized that the introduction of chemisorbed oxygen species during the ADS process could increase the sorption capacity for TiO 2 -CeO 2 mixed oxides.…”
mentioning
confidence: 99%
“…Pure anatase and Ce-doped anatase (001) surfaces were considered. A Ti 16 O 32 cell with four layers of TiO 2 was used for the calculation. The top two layers were relaxed during the optimization.…”
mentioning
confidence: 99%
See 1 more Smart Citation